A low cost smart security and home automation system employing an embedded server and a wireless sensor network - (:unkn) unknown (IEEE Computer Society, 2016)
The advances in embedded technology and automation makes the human daily life easier. In this study, a smart home is presented an application including sensor and controller nodes connected to the custom design local wireless network. User reaches to the system using a web-base interface or using a smart phone application. We tested our system through conducted experiments and the results will be presented in the paper. The proposed system is a complete, low cost and user-friendly design for monitoring and remote control purposes. © 2016 IEEE.
Keywords: internet interface; Smart home; temperature control; wireless communication